Trick or treatment : the undeniable facts about alternative medicine - Singh, Simon; Ernst, E. (Edzard) (New York : W.W. Norton, 2008)
In this groundbreaking analysis, over thirty of the most popular treatments--acupuncture, homeopathy, aromatherapy, reflexology, chiropractic, and herbal medicines--are examined for their benefits and potential dangers. Questions answered include: What works and what doesn't? What are the secrets, and what are the lies? Who can you trust, and who is ripping you off? Can science decide what is best, or do the old wives' tales really tap into ancient, superior wisdom? In their scrutiny of alternative and complementary cures, authors Simon Singh and Edzard Ernst also strive to reassert the primacy of the scientific method as a means for determining public health practice and policy.--From publisher description.
How do you determine the truth? -- The truth about acupuncture -- The truth about homeopathy -- The truth about chiropractic therapy -- The truth about herbal medicine -- Does the truth matter?
Includes bibliographical references (p. 329-331) and index.
Keywords: Alternative medicine; Complementary Therapies; Evidence-Based Medicine; Placebo Effect